-6w-2(-2x+5w)+5x=

Simple and best practice solution for -6w-2(-2x+5w)+5x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6w-2(-2x+5w)+5x= equation:


Simplifying
-6w + -2(-2x + 5w) + 5x = 0

Reorder the terms:
-6w + -2(5w + -2x) + 5x = 0
-6w + (5w * -2 + -2x * -2) + 5x = 0
-6w + (-10w + 4x) + 5x = 0

Combine like terms: -6w + -10w = -16w
-16w + 4x + 5x = 0

Combine like terms: 4x + 5x = 9x
-16w + 9x = 0

Solving
-16w + 9x = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-16w + 9x + -9x = 0 + -9x

Combine like terms: 9x + -9x = 0
-16w + 0 = 0 + -9x
-16w = 0 + -9x
Remove the zero:
-16w = -9x

Divide each side by '-16'.
w = 0.5625x

Simplifying
w = 0.5625x

See similar equations:

| -4(v-1)=5v-32 | | 20k+20=-20+18k | | 5x-4=5(x-2) | | h^2-8h-9=0 | | 2X-4=4y | | -7u-35=7(u-7) | | 2.7x+6.1+3.2-4.9= | | 2[x+4]=-5x+1 | | 7w-1=14+1+7w | | 8+3x=4x+5+2 | | 10x-2y=0 | | 5d^2+46d+9=0 | | xp+xq=r | | -7(u-5)=-3u+3 | | -8-9z=-3-10z | | 5x+6=10y | | 8s^2+33s+4=0 | | 2x+y=7*y | | 6-6h=10-4h | | 4u+16=72 | | 4x+16=8(x-1) | | 9(3n+2)=8(8n+6)+4 | | 9(2p-3)=171 | | 3s=30 | | 7f+1=9+6f | | 270=10x+100 | | 35=30 | | Z=7 | | -3+9v=-2+8v | | 7c+5=5+7c | | -10s+10=-9s | | 9a+6.75c=1406.25 |

Equations solver categories